Fish Diversity and Phylogenetics in the Lakes of Bromo Tengger Semeru National Park Based on eDNA - Chuanata, Wilsen; Susilowati, Ari; Budiharjo, Agung; Travis, Justin M. J. (Universitas Negeri Semarang, 2025)
Indonesia is home to 1,248 species of freshwater fish, which play a vital role in sustaining the ecosystem. Lakes Ranu Pani, Ranu Regulo, and Ranu Darungan, located within the Bromo Tengger Semeru National Park, lack data on freshwater fish. This study aimed to assess fish diversity in these lakes using environmental DNA (eDNA) metabarcoding and to establish phylogenetic relationships among the species present. Water samples were filtered using 0.45 µm mixed cellulose ester filter paper, after which the collected DNA was extracted utilizing a DNA miniprep kit. The 12S rRNA gene was amplified using the MiFish primer, and the amplicon DNA was sequenced with the Illumina MiSeq 2x250 platform. The sequences were aligned using Blast+ for species identification and subsequently analyzed for alpha and beta diversity. A phylogenetic tree was constructed with MEGA12. The findings revealed eight species from five families, with Gambusia affinis being the most abundant. Ranu Pani exhibited low species diversity, while Ranu Regulo and Ranu Darungan displayed moderate diversity. Beta diversity analysis indicated similarities between Ranu Pani and Ranu Regulo, but distinct communities were found in Ranu Darungan. Phylogenetic analysis showed close relationships between species from the Cichlidae and Osphronemidae families, while a more distant relationship was observed with the Cyprinidae family. These baseline data can serve as a reference for future research on developing conservation strategies, monitoring environmental changes, and supporting biodiversity management.